All the divine names and titles in the Bible : a unique classification of all scriptural designations of the three persons of the Trinity - Lockyer, Herbert, 1886- (London, UK : Pickering and Inglis, 1975)
Includes bibliographical references and index.
Brethren writer.
Keywords: Names of God